ANALISIS EFEKTIFITAS PROGRAM PINJAMAN DANA BERGULIR PADA UNIT PENGELOLA KEGIATAN (UPK) PNPM MANDIRI DI KECAMATAN MOJOWARNO KABUPATEN JOMBANG TAHUN 2014 - Taufik H, Agus (Universitas Islam Negeri Sunan Kudus, 2015)
This study aims to analyze the effectiveness of activities revolving Unit Pengelola Kegiatan (UPK) Mojowarno subdistrict PNPM Mandiri in 2014. Indicators used to measure effectiveness is in the form of performance instrument measuring the ratio CCR, ROI, PAR, LAR.This type of research is qualitative descriptive. This study uses secondary data derived from the financial statements in the form of funds flow statement, balance sheet and income statement in 2014. The data was analyzed using a model of Miles and Huberman. Results of analysis of the effectiveness of the CGU districts Mojowarno 2014 indicate that the value CCR> 125% is equal to 219%, which means an effective, ROI figures show 26% are categorized as effective as> 10%, PAR is considered effective because the value obtained <10% is equal to 6 %, and LAR in the category are not effective because of ≥20%, ie by 21%.